2010
DOI: 10.1097/aap.0b013e3181fa1163
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Klebsiella pneumoniae and Enterobacter aerogenes Bacteremia After Interventional Pain Management Procedures, New York City, 2008

Abstract: Infection was associated with pain management procedures, specifically those involving injection to the sacroiliac joint. Lapses in infection control likely led to the contamination of single-use vials that were then used for multiple patients. Reuse of medication vials should be restricted, and affordable single-dose vials should be made available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…28 With regard to infectious complications, risks tend to rise in immunocompromised patients, with prolonged epidural catheterization, when the proceduralist unknowingly harbors virulent nasopharyngeal pathogens and does not wear a mask, and/or when practitioners breach aseptic technique. 7,28,[37][38][39][40] Table 2 lists studies reported since 1990 that document incidences of neuraxial injury (often combining hematoma, infection, direct spinal cord injury, etc). These studies point to several common themes.…”
Section: Incidence Of Neuraxial Injurymentioning
confidence: 99%
“…28 With regard to infectious complications, risks tend to rise in immunocompromised patients, with prolonged epidural catheterization, when the proceduralist unknowingly harbors virulent nasopharyngeal pathogens and does not wear a mask, and/or when practitioners breach aseptic technique. 7,28,[37][38][39][40] Table 2 lists studies reported since 1990 that document incidences of neuraxial injury (often combining hematoma, infection, direct spinal cord injury, etc). These studies point to several common themes.…”
Section: Incidence Of Neuraxial Injurymentioning
confidence: 99%
“…7e9 Although individual cases of infection are uncommon, outbreaks of infection associated with contaminated epidural or intra-articular injections are even more unusual. During the past decade, such examples include three outbreaks of Serratia marcescens infection associated with epidural or intra-articular injections, 10e12 an outbreak of Klebsiella pneumoniae and Enterobacter aerogenes bacteremia after sacroiliac (SI) joint steroid injections, 13 an outbreak of Exophiala dermatitidis infection after epidural and intraarticular steroid injections, 14 and an outbreak of Aspergillus meningitis after spinal anesthesia for caesarean section. 7 The largest of these outbreaks involved 11 patients.…”
mentioning
confidence: 99%
“…[14][15][16][17] A matter of particular concern is the infection risk due to unsafe injection practices that are associated with the use of single-dose vials for multiple patients [18][19][20] and the use of multi-dose vials. [6][7][8][9] International guidelines on preventing contamination of anaesthetic-associated medication 21,22 clearly state that preservative-free vials are single-patient, single-dose items.…”
mentioning
confidence: 99%